Pengaruh Capital Adequacy Ratio (CAR), Biaya Operasional Pendapatan Operasional (BOPO), Non Performing Loan (NPL), Dan Loan To Deposits Ratio (LDR) Terhadap Return On Assets (ROA) Pada PT. Bank Rakyat Indonesia (Persero) Tbk - Ayu Wulandari; Alwi; Aliah Pratiwi (PENG: Jurnal Ekonomi dan Manajemen, 2024)
This research aims to determine the effect of Capital Adequacy Ratio (CAR), Operating Costs, Operating Income (BOPO), Non-Performing Loans (NPL) and Loan To Deposits Ratio (LDR) on Return On Assets (ROA) at PT. Bank Rakyat Indonesia (Persero) Tbk. The type of research used is associative. The research instrument used was the annual report of PT. Bank Rakyat Indonesia (Persero) Tbk for 10 years from 2013 to 2022 with the data used namely net profit, non-performing loans, operational costs, risk-weighted assets, and credit granted. Population used in this research is the annual report for 2003-2022. The sample size is 10 years, namely from 2013-2022. The sample selection in this research used a non-probability sampling technique with purposive sampling technique. The data collection techniques used in this research are documentation and literature study. The data analysis techniques used are the classical assumption test, multiple linear regression analysis, correlation coefficient, determination test, t test and f test. The research results show that the Capital Adequacy Ratio (CAR), Operating Costs, Operating Income (BOPO), Non-Performing Loans (NPL), and Loan to Deposits Ratio (LDR) do not have a significant effect, partially or simultaneously, on Return On Assets (ROA) in PT. Bank Rakyat Indonesia (Persero) Tbk.